Jaringan Syaraf Tiruan Memprediksi Kebutuhan Alat Suntik Medis di Rumah Sakit Menggunakan Metode Backpropagation: (Studi Kasus : RSU BATHESDA) - ramli, Ramli; Nurhayati, Nurhayati; Saragih, Rusmin (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
The hospital is an integral part of a social and health organization with the function of providing services, disease healing and disease prevention to the community. Predicting the number of medical devices is essential for managing a hospital, managing human and financial resources, and for properly distributing material resources. If the number of medical devices can be predicted accurately, this will become the basis for planning and making decisions for hospital managers. Based on these reasons, an electronic tool is needed that can determine the number of medical device needs with a high degree of accuracy and the display of the results for easy reading and data collection. From system testing, the need for medical devices in the following month will decrease in providing some medical devices because they still have a lot of stock in the previous month. The Backpropagation Algorithm can carry out the prediction process, but whether or not the error value and the output is very much influenced by the determination of parameters such as the amount of learning rate and the number of neurons in the hidden layer.